Self care behavior of hypertension patients who live in Muang district, Chumphon province - Juntanon, Naowarat; Singchai, Butsarakham; Worawong, Wiwat (Asia-Pacific Journal of Science and Technology, 2017)
The purpose of this study was to investigate the self care behavior of hypertension patients who live in Muang district, Chumphon province by the comparison of the self care behaviors based on their personal and supportive factors. The studied subjects were 367 participants, randomly selected with stratifying and proportional methods and questionnaires were used for data collection. The data were analyzed with statistical methods to determine frequency, percentage, mean and standard deviation, lowest and highest values, t-test, and one-way ANOVA. The results showed that their behavior of self care performed as the whole was at a high level as the patients cared for themselves by taking drugs as the doctor recommendation. Difference in gender and having direct-inherited hypertension relatives of the patients yielded different self care behavior significantly at 0.05. Difference in having supportive factors of knowledge and belief on hypertension disease and social support did yield different self care behavior of the hypertension patients significantly at 0.01.